Snort 2.1 Intrusion Detection, Second Edition - Beale, Jay (Syngress Publishing, 2011)
Called "the leader in the Snort IDS book arms race" by Richard Bejtlich, top Amazon reviewer, this brand-new edition of the best-selling Snort book covers all the latest features of a major upgrade to the product and includes a bonus DVD with Snort 2.1 and other utilities.